Neuromuscular maturation in the neonate: Combined electroneurographic and ultrasonographic study. (February 2020) - Lori, S.; Bertini, G.; Gabbanini, S.; Bastianelli, M.; Cossu, C.; Lolli, F.; Dani, C.
Abstract: Background: The combined electroneurography and muscle ultrasound examination (ENG-USM) in adult patients showed a correlation between the compound motor action potential (CMAP) and muscular thicknesses (MT). No similar studies exist regarding the neonatal period. Aim: To evaluate the correlations between the maximum compound muscle action potential (CMAP) and maximum muscle thickness (MT) in term and premature newborns versus a group of young adults, as measured by combined electroneurography-ultrasonography (ENG-USM) to assess the stages. Study design: Observational cohort study. Subjects: We studied 36 subjects (14 premature and 11 term infants, and 11 young adults), who underwent ENG-USM of the tibialis anterioris (TA) muscle. Outcome measures: We measured: 1) Onset-Peak (O-P) and Peak-to-Peak (P-P) maximum CMAP; 2) maximum MT; and 3) MT at the detected maximum CMAP. Results: The maximum CMAP in term newborns studied was about 1/3 of the mean value measured in the adults; the differences between O-P and P-P values of the term versus premature infants were not significant. We did not find a good correlation between maximum MT and maximum CMAP in the term ( r = 0.63) newborns, contrary to what was found in preterms ( r = 0.95) and in young adults ( r = 0.98). Conclusion: Our ENG-USM study shows that in newborns, the site of innervation of the neuromuscular plaque does not correspond to MT since muscle growth is related to the period of development, and depends on the progression of the nerve terminal branches that go to innervate the same muscle. Highlights: The combined ultrasonography and electroneurography method was applied in neonates. This method allows to investigate neuromuscular morpho-functional maturation. Unlike to adult, the maximum muscle thickness and CMAP do not coincide in the newborn. The neuromuscular normative data plays a role for nerve and muscle early damage.